2022
DOI: 10.3390/molecules27061851
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Constituents and Pharmacological Potential of Tamus communis Rhizomes

Abstract: Tamus communis L. is a plant distributed in a number of geographical areas whose rhizome has been used for centuries as an anti-inflammatory and analgesic remedy. This review aims to summarize the current knowledge of the chemical composition and biological activity of the extracts or individual compounds of the rhizome. The data for the principal secondary metabolites are systematized: sterols, steroidal saponins, phenanthrenes, dihydrophenanthrenes, etc. Results of biological tests for anti-inflammatory acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 55 publications
(111 reference statements)
0
3
0
1
Order By: Relevance
“…The 4-hydroxybenzoic acid showed a noncompetitive mode of inhibition while apigenin and kaempferol inhibited XO competitively and reversibly (Loh et al, 2022). Slavova et al (2022) isolated compounds from the extracts of Tamus communis rhizomes to evaluate inhibitory activity against XO. Compounds, 5,8-dimethoxypsoralen (IC 50 = 0.099 ± 0.002 mg/mL) and heraclinin (IC 50 = 0.074 ± 0.003 mg/mL) were found to inhibit XO concentration dependently.…”
Section: Phytochemicalsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 4-hydroxybenzoic acid showed a noncompetitive mode of inhibition while apigenin and kaempferol inhibited XO competitively and reversibly (Loh et al, 2022). Slavova et al (2022) isolated compounds from the extracts of Tamus communis rhizomes to evaluate inhibitory activity against XO. Compounds, 5,8-dimethoxypsoralen (IC 50 = 0.099 ± 0.002 mg/mL) and heraclinin (IC 50 = 0.074 ± 0.003 mg/mL) were found to inhibit XO concentration dependently.…”
Section: Phytochemicalsmentioning
confidence: 99%
“…Moreover, some compounds in the extracts displayed a superoxide radical scavenging effect. Subsequently, the relationship between the phenolic content, XO inhibition, and antioxidant activity showed that these activities were based on the phenolic compounds in the testify fractions (Slavova et al, 2022). Liu et al (2022) identified XO inhibitors from pickled radish compounds.…”
Section: Phytochemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ancak bitkinin kökleri üzerinde yapılan fitokimyasal çalışmalar fenantren ve 9,10-dihidrofenantren (nudol, konfusarin, krizotoksen, herorensol, orkinol gibi) bakımından zengin olduğunu göstermiştir. Ayrıca β-sitosterol, stigmasterol ve kampesterol gibi steroller taşıdığı da bilinmektedir [31]. Bildiğimiz kadarıyla fenatrenlerin üreaz enzimi üzerindeki etkisi henüz değerlendirilmemiştir ancak daha önceki bir çalışmada sterol yapısındaki ursolik asidin üreaz enzimini %52 oranında inhibe ettiği gösterilmiştir [32].…”
Section: Tablo 3 çAlışılan Bitkilerin Total Fenol Ve Flavonoit Içerik...unclassified